Anti-Depressant Effects Of Withania Somnifera Fat (Ashwagandha Ghrutha) Extract In Experimental Mice - JAYANTHI MK,; PRATHIMA C,; HURALIKUPPI JC,; SURESHA RN,; MURALI DHAR, (International Journal of Pharma and Bio Sciences, 2012)
Anti-depressants play a major role in today’s life style. There are evidences of the ayurvedic formulation Ashwagandha ghrutha (AGG, fat extract) being effective in various neuro- psychiatric conditions. The anti-depressant activity of Withania somnifera (AGG) was studied using 3 models, Behavioral despair tests- Forced swim test (FST), Tail suspension test (TST) and Anti-reserpine test. Effect of different doses of AGG (20, 40mg/kg), Imipramine (15mg/kg) and their combination (10mg/kg each) were studied on behavioral despair tests induced immobility time and reserpine antagonism. WS produced dose dependent decrease in immobility time in chronic studies in FST and TST model, maximum effect being observed with WS 40 mg/kg. On anti-reserpine models, ptosis, catatonia and sedation scores in the standard, test and combination drug groups were significantly different from the control group. The findings support the use of WS as potential adjuvant in depressive disorders.